The Study Of Cargo Crime During Road Transportation In Malaysia: Application Of Routine Activities Theory - Ching, Eng Leong (2019)
The studies on crime prevention, causes of crime and the theories associated with it are very essential in criminology. Routine Activities Theory is also the basis for many criminological theories. Although it has some shortcomings, it is still a strong theory that the theorists and practitioners on crime prevention can benefit from. This study explained the use of routine activities theory in preventing and reducing cargo crime on road transportation in Malaysia. The objectives of this study were to provide information related to this theory and investigate its relationship with the prevention of cargo crime. Security threats and risk on road transportation in Malaysia are the pressing concerns that are currently being faced by the industry. This study was conducted to identify the security control measures implemented by cargo transportation companies in Malaysia to prevent cargo crime. The relationships between the variables were addressed and established to find out how the independent variables are related to the dependent variables. Correlation analysis was conducted to determine the relationship between foreign and local cargo road transportation companies on the implementation of security control measures. Survey was conducted along PLUS Highway Malaysia to identify security control measures on truck parking facilities by measuring the level of the lighting condition, the availability of guarding services and the installation of security equipment.